Kinetic studies on RAFT inverse-suspension smart hydrogels formation using a tetra detector array - Gonçalves, Miguel A.D. (2013)
Temperature/pH stimuli-responsive hydrogel particles were synthesized using inverse-suspension polymerization in batch stirred reactor. Different water soluble comonomers were present in the initial mixture (namely N-isopropylacrylamide and acrylic acid) as well as crosslinkers with different functionalities (bi-, tri- and tetrafunctional) so that their effect on the network crosslinking density could be seen. Different operating conditions such as polymerization temperature (in the range 20 to 70 °C), monomers dilution, neutralization and the inilial ratios 01 co-monomers and monomers/crosslinker were also tried. Classical Iree-radical polymerization (FRP) and RAFT polymerization (e.g. using 4-cyano-4-phenylcarbonothioylthio-pentanoic acid) were compared in order to put into evidence the impact of the polymerization mechanism on the hydrogel molecular architecture. Sampling at different polymerization limes allowed the study of the kinetics of gel formalin through the analysis by SEC of the soluble phase. RI, LALLS, Intrinsic Viscosity and UV signals were simultaneously measured using a tetra-detector array, thus yielding absolute molecular weight, branching factors, hydrodynamic radius and radius 01 gyration. The performance 01 hydrogel beads was assessed through drug delivery tests triggered by changes in the environmental temperature/pH. Aiming at the development of tools hopefully useful for the design of such advanced materials, a general kinetic approach (Chem. Eng. Sci. 2005, 60, 423) was used to carry out modeling studies including consideration of finite loop formation reactions.